PERCOBAAN FRAKSIONASI DISTILASI MINYAK KENANGA DARI CIREBON - Bambang Wiyono; Mohammad Rosid (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
The purpose of the research is to study the properties of fractional distilled cananga oil compared with Indonesia Industrial Standard requirement for cananga oil and with ylangylang oil properties of the third fraction (the lowest quality of ylangylang oil). The fractionation based on the distilling times, these were first fraction 0 7 hours, second fraction 8 14 hours, and third fraction 15 24 hours.The results indicated that third fraction have met with Indonesia Industrial Standard requirement, but specific gravity of the first and second fraction have not met the requirement. Acid number of all fraction have met requirement for ylangylang oil. Ester number of the third fraction proximated the ester of ylangylang oil. Ester number and ester content of the first fraction had a higher than the second fraction and this fraction had a higher than the third fraction. So, the first fractional distilled cananga oil possesed the highest quality. These quality could be increased by the fractional steam distillation in vacum pressure, and the distilling used fresh cananga flowers.